Traumatic Posterior Urethral Strictures in Children and Adolescents - Podesta, Miguel; Podesta, Miguel (Frontiers in Pediatrics, 2019)
Background Management of partial or complete traumatic urethral disruptions of the posterior urethra in children and adolescents, secondary to pelvic fracture poses a challenge. Controversy surrounds the acute treatment of posterior urethral injuries and the delayed management of pelvic fracture posterior urethral distraction defects (PFPUDDs). We reviewed the urological literature related to the treatment of traumatic posterior urethral injuries and delayed repair of urethral distraction defects in children and adolescents. Material and Methods There are few long-term outcomes studies of patients who underwent PFPUDDs repairs in childhood; most published reports included few cases with short followup. We excluded studies in which the pediatric cohort of patients was heterogeneous in terms of stricture disease, etiology and location. Results Primary cystostomy and delayed urethroplasty is the traditional management for posterior urethral injuries. Immediate repair is rarely possible to perform. Realignment of posterior urethral rupture in children is indicated in special situations: a) concomitant bladder neck tears trying to preserve competence of the proximal sphincter, b) associated rectal lacerations and c) long disruptions of the torn urethral ends. Before delayed reconstruction ascending urethrography and micturating cystourethrogram along with retrograde and antegrade urethroscopy define the site and length of the urethral gap. However, the most accurate evaluation of the anatomical characteristics of the distraction defect is made when surgical exposure reveals the complexity of the ruptured urethra. Partial ruptures may be managed with endoscopic urethral stenting or suprapubic cystostomy, which may result in a patent urethra or a short stricture treated by optical urethrotomy. The gold standard treatment for PFPUDDs in children is deferred excision of pelvic fibrosis and bulbo-prostatic tension-free anastomosis, provided a healthy anterior urethra is present. Timing of delayed repair is at 3 to 4 months after trauma. Some urologists prefer either the perineal access alone or the transpubic approach to restore urethral continuity in children with PFPUDDs. Conclusion As evidenced in this review the perineo-abdominal partial transpubic progressive anastomotic repair has advantages over the isolated perineal anastomotic approach in patients with “complex” PFPUDD. The former approach provides wider exposure and facilitates reconstructionr of long or complicated posterior urethral distraction defects.